Investigation of Binding‐Site Homology between Mushroom and Bacterial Tyrosinases by Using Aurones as Effectors. Issue 9 (21st May 2014) - Haudecoeur, Romain; Gouron, Aurélie; Dubois, Carole; Jamet, Hélène; Lightbody, Mark; Hardré, Renaud; Milet, Anne; Bergantino, Elisabetta; Bubacco, Luigi; Belle, Catherine; Réglier, Marius; Boumendjel, Ahcène
Abstract Tyrosinase is a copper‐containing enzyme found in plants and bacteria, as well as in humans, where it is involved in the biosynthesis of melanin‐type pigments. Tyrosinase inhibitors have attracted remarkable research interest as whitening agents in cosmetology, antibrowning agents in food chemistry, and as therapeutics. In this context, commercially available tyrosinase from mushroom (TyM) is frequently used for the identification of inhibitors. This and bacterial tyrosinase (TyB) have been the subjects of intense biochemical and structural studies, including X‐ray diffraction analysis, and this has led to the identification of structural homology and divergence among enzymes from different sources. To better understand the behavior of potential inhibitors of TyM and TyB, we selected the aurone family—previously identified as potential inhibitors of melanin biosynthesis in human melanocytes. In this study, a series of 24 aurones with different hydroxylation patterns at the A‐ and B‐rings were evaluated on TyM and TyB. The results show that, depending on the hydroxylation pattern of A‐ and B‐rings, aurones can behave as inhibitors, substrates, and activators of both enzymes. Computational analysis was performed to identify residues surrounding the aurones in the active sites of both enzymes and to rationalize the interactions. Our results highlight similarities and divergence in the behavior of TyM and TyB toward the same set of molecules.